PENERAPAN MODEL VISUAL, AUDITORY, KINESTHETIC (VAK) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA SEKOLAH DASAR - Dinita, Sonia; Aprinawati, Iis; Fadhilaturrahmi, Fadhilaturrahmi; Nurhaswinda, Nurhaswinda; Marta, Rusdial (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This study investigated the effectiveness of the Visual, Auditory, Kinesthetic (VAK) model in improving the initial reading skills of grade 1 students at SDN 007 Bangkinang Kota. The research was motivated by the low reading ability observed in this group of students. Employing a class action research (PTK) design with two cycles, the study involved 26 students (13 male and 13 female). Each cycle consisted of two meetings and four stages: planning, implementation, observation, and reflection. Data collection, conducted in July 2023, utilized documentation and observation techniques, analyzed qualitatively and quantitatively. Instruments included teacher and student activity observation sheets, and student worksheets. Pre-action results revealed a learning completeness rate of only 30.76%. Following the implementation of the VAK model, this rate progressively increased across both cycles. By the end of cycle II, meeting II, the learning completeness rate reached 92.30%, with 24 students achieving mastery. These findings suggest that the VAK model holds significant potential for enhancing initial reading abilities in grade 1 students